Association between neutrophil to lymphocyte ratio with the severity of coronary artery diseases - Das, Saurav; Das, Prabir Kumar; Awal, Anisul; Bin Latif, Sayem; M. Ismail, Khondaker; Hossan, M. Sawkat; Siddike, Sohel; Paul, Swarna; Bashiruddin, M. A. B. K.; Bhattacharyya, Partha (International Journal of Research in Medical Sciences, 2023)
Background: Coronary artery disease is a type of heart disease where the arteries of the heart cannot deliver enough oxygen-rich blood to the heart. This study aimed to evaluate the association between neutrophil to lymphocyte ratio (NLR) with the severity of coronary artery diseases. Methods: This cross-sectional study was conducted in the Department of Cardiology, Chittagong Medical College Hospital, Chattogram, Bangladesh during the period from 1 July 2020 to 31 June 2021. 160 patients undergoing elective coronary angiography with the symptoms of coronary artery disease were enrolled in this study. A purposive sampling technic was used. The association between NLR and Gensini score was assessed using Pearson’s or Spearman’s correlation analysis as appropriate. All data were processed, analyzed and disseminated by using MS Excel and SPSS version 23.0 program as per necessity. Results: The mean (±SD) Gensini score of our participants was 42.75 (±29.50) and the mean (±SD) NLR (Neutrophil-lymphocyte ratio) was 2.38 (±1.11). In this study, the AUROC for NLR was found as 0.851 with a P-value of <0.001, indicating a statistically significant association of NLR with the severity of CAD. The scatter dot diagram showed the correlation between NLR and Gensini score. Both the variables were positively correlated and the degree of correlation was found statistically significant (r=0.44; p<0.001) by Pearson’s correlation test. The multivariate logistic regression analysis showed that a high level of NLR had an independent association with severe CAD (with OR being 3.308) along with dyslipidemia. Conclusion: High blood NLR is associated with the severity of CAD and it may be useful for predicting angiographically severe disease.